2011
DOI: 10.1590/s0037-86822011005000031
|View full text |Cite
|
Sign up to set email alerts
|

Risco de transmissão do vírus da raiva oriundo de sagui (Callithrix jacchus), domiciliado e semidomiciliado, para o homem na região metropolitana de Fortaleza, estado do Ceará

Abstract: Introduction:In the State of Ceará, a new variant of the rabies virus was identified associated with cases of human rabies transmitted by common marmosets (Callithrix jacchus), which are frequently kept as pets. This new variant does not present antigenic proximity or genetic relationship to variants of the virus isolated from bats and terrestrial mammals from the American continent. The present study aimed to evaluate the risk factors of rabies virus transmission from common marmosets (C. jacchus) maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
9
0
7
Order By: Relevance
“…The non-human primates are reservoirs of various zoonoses including rabies, and the involvement of monkeys in human accidents shows that Cebus (monkey-nail) and Callithrix (sagui) are among the most frequent species (Ramos et al, 2002). The population in Brazil is aware that dogs and cats can transmit rabies, but many do not know that bats, monkeys and other wild animals are also transmitters of the disease, so when they are bitten by these animals, they do not seek medical care and are at serious risk of being victims of the disease (Aguiar et al, 2011). It is important to note that laboratory surveillance of Yellow Fever in Brazil should take into account the diagnosis of rabies primarily in those primates that are sent for the confirmation of yellow fever in episodes of epizootics and/or outbreaks including human cases.…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 99%
“…The non-human primates are reservoirs of various zoonoses including rabies, and the involvement of monkeys in human accidents shows that Cebus (monkey-nail) and Callithrix (sagui) are among the most frequent species (Ramos et al, 2002). The population in Brazil is aware that dogs and cats can transmit rabies, but many do not know that bats, monkeys and other wild animals are also transmitters of the disease, so when they are bitten by these animals, they do not seek medical care and are at serious risk of being victims of the disease (Aguiar et al, 2011). It is important to note that laboratory surveillance of Yellow Fever in Brazil should take into account the diagnosis of rabies primarily in those primates that are sent for the confirmation of yellow fever in episodes of epizootics and/or outbreaks including human cases.…”
Section: Carollia Perspicillata D Rotundus and A Lituratusmentioning
confidence: 99%
“…1 Domesticated dogs are mainly responsible for rabies transmission, especially in Asian and African countries, but other wild mammals such as bats, nonhuman primates, foxes, and wild dogs can be responsible for human cases. [2][3][4][5] Pathological studies have shown that animal and human brains infected with rabies virus (RABV) develop encephalitis but exhibit only minimal neuronal loss and varying degrees of inflammation, [6][7][8] thus demonstrating that the virus has mechanisms to evade the host immune response. 9 An uninfected animal's central nervous system (CNS) has intact endothelial tight junctions, low expression of adhesion molecules, and lack of immunological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Classic RABV is maintained by terrestrial mammals worldwide, except in Australia, Antarctica, and several islands, and by bats in the New World only. 1 In Brazil rabies is still endemic and independent cycles have been identified in a range of species, such as marmosets (Callithrix jacchus), 3,4 in many wild carnivores, crab eating fox (Cerdocyon thous), Pseudalopex vetulus, 5,6 Dusicyon vetulus, 7 and many bat species. 8 Rabies is almost an invariably fatal disease, having the highest case fatality rate of any currently recognized infectious diseases.…”
Section: Introductionmentioning
confidence: 99%